2021
DOI: 10.3390/nu13030801
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maternal Weight in the Hierarchy of Macrosomia Predictors; Overall Effect of Analysis of Three Prediction Indicators

Abstract: So far it has not been established which maternal features play the most important role in newborn macrosomia. The aim of this study is to provide assessment of a hierarchy of twenty six (26) maternal characteristics in macrosomia prediction. A Polish prospective cohort of women with singleton pregnancy (N = 912) which was recruited in the years 2015−2016 has been studied. Two analyses were performed: for probability of macrosomia >4000 g (n = 97) (vs. 755 newborns 2500−4000 g); and for birthweight >90th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
3
16
0
2
Order By: Relevance
“…The risk profiles were not assessed in any study. Many previous studies confirmed the associations between a higher macrosomia risk and maternal obesity [13][14][15]17,18,20] or between fetal growth restriction (FGR) risk and maternal obesity [3,18,25,33] or underweight [33][34][35]. However, these studies were retrospective and also did not include subgroup analyses or risk profiles (as was the case in our study).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The risk profiles were not assessed in any study. Many previous studies confirmed the associations between a higher macrosomia risk and maternal obesity [13][14][15]17,18,20] or between fetal growth restriction (FGR) risk and maternal obesity [3,18,25,33] or underweight [33][34][35]. However, these studies were retrospective and also did not include subgroup analyses or risk profiles (as was the case in our study).…”
Section: Discussionsupporting
confidence: 76%
“…Interventions should be multi-directional (involving diet, physical activity, and health-promoting behavior) and should be carried out by multidisciplinary teams [1]. Dietary guidelines (worldwide and in Poland) for pregnant women have been described in our previous works [4,13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations